Uma abordagem de ensino de leitura crítica: implicações para a formação identitária de leitores - Nogueira, Sandra Helena Gonçalves (2010)
This thesis focuses on the study of reading comprehension of literary texts by means of the practice of group think-aloud (Zanotto, 1998), thus allowing for the creation of room for critical reading to take place by students of the 8th grade Elementary School in Sao Paulo. Since literary texts often present metaphors, and considering that a number of Brazilian public schools do not train students on such reading abilities (Kleiman, 1998), I sought deeper theoretical background on the new view of conceptual metaphor (Lakoff & Turner,1989) with the aim of contributing to the development of reading comprehension of literary texts. The research carried out followed the critical action research methodology (Kincheloe, 1997), within the qualitative research paradigm, interpretative in nature (Bortoni-Ricardo, 2008). The investigation focused on my own actions as a mediator of the students voices whilst these were thinking aloud in groups on the subjects of the literary texts being interpreted in the classroom. The instruments used to collect data were the technique of group think aloud as well as reflective diaries. Data analysis investigated the paths taken by the students of this Elementary School class, considering the importance of metaphors as revealing instances of the human aptitude for making sense (Steen, 1994), and taking into account that the reader, within their cultural context, has the subjective freedom to understand the metaphoric effect. The school universe, stage of great cultural diversity, is the appropriate environment for the development of the social, cultural and identity nature of the students. Results show the mechanisms employed by the readers to understand and interpret the texts that develop the students critical reading. Results also show that the group think-aloud fostered spaces for the argumentation of ideas, besides stimulating the reflection of aspects of identity, and facilitating the understanding of the metaphors found in the literary texts